Ocena ranljivosti gozdnih tal na zbijanje zaradi mehanizacije - preizkus in nadgradnja terenske metode blatne kepe - Anton Poje (Slovenian Forestry Institute, 2020)
In recent decades, the use of heavy machinery in forest management has increased, causing compaction and alternations in soil morphology. As soil vulnerability to compaction is highly dependent on the type of soil and the current soil water content, rapid assessment of the suitability of the conditions for the use of machinery is of great importance for practice. The article discusses methods for rapidly determining the mechanical properties of soil. We tested the soil clump method, which was supplemented by the assessment of the appearance of the hand and handprint during preparation of the soil clumps, soil water content measurements and determination of the lower and upper limits of soil plasticity. The following soil types, which are common in Slovenian forest stands, were selected: brown soil on limestone and dolomite (Eutric Cambisol), dystric brown soil (Dystric Cambisol) and hypogley (Eutric Gleysol). The results of the study showed that, when dropped, the surface area of the clump increases with the water content of the soil, while at the same time the appearance of the clump, the soil residue on the hands and the appearance of the handprint change. Evaluation of the appearance of the hands and handprint represent supplements to the existing clump method, but can also be an alternative to it, as they can be both used independently. By determining the lower and upper limits of plasticity or soil strength, we indirectly assessed the risk of soil damage in forest production. Through the use of soil condition indicators, such as the appearance of the soil clump, the soil residue on the hands and the appearance of the handprint, we can quickly and easily assess the current working conditions in practise and thus prevent excessive soil deformation in forest operations.